2016
DOI: 10.1104/pp.16.00059
|View full text |Cite
|
Sign up to set email alerts
|

The De-Etiolated 1 Homolog of Arabidopsis Modulates the ABA Signaling Pathway and ABA Biosynthesis in Rice

Abstract: DEETIOLATED1 (DET1) plays a critical role in developmental and environmental responses in many plants. To date, the functions of OsDET1 in rice (Oryza sativa) have been largely unknown. OsDET1 is an ortholog of Arabidopsis (Arabidopsis thaliana) DET1. Here, we found that OsDET1 is essential for maintaining normal rice development. The repression of OsDET1 had detrimental effects on plant development, and leaded to contradictory phenotypes related to abscisic acid (ABA) in OsDET1 interference (RNAi) plants. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…qFWn7 located in the same interval with OsFLW7 identi ed by Xu et al (2017). Known genes OsBAK1 (Li et al, 2009), SNFL1 (He et al, 2018) and OsDET1 (Zang et al, 2016), were found to be located within or nearby the LD interval of qFWn8, qFWn5-2, qFLAn1-2 in this study. Among these genes, OsBAK1 controlling leaf angle and length by regulating brassinosteroid (BRs), and has been observed signi cantly reduce plant height.…”
Section: Discussionsupporting
confidence: 60%
“…qFWn7 located in the same interval with OsFLW7 identi ed by Xu et al (2017). Known genes OsBAK1 (Li et al, 2009), SNFL1 (He et al, 2018) and OsDET1 (Zang et al, 2016), were found to be located within or nearby the LD interval of qFWn8, qFWn5-2, qFLAn1-2 in this study. Among these genes, OsBAK1 controlling leaf angle and length by regulating brassinosteroid (BRs), and has been observed signi cantly reduce plant height.…”
Section: Discussionsupporting
confidence: 60%
“…For ABA and Cd treatments, the roots of the three-week-old hydroponic rice seedlings were immersed in Yoshida’s culture solution containing either 50 µM ABA [ 59 , 60 , 61 ] or 50 µM Cd for 24 h [ 62 ]. For cold stress, rice seedlings were exposed to 4 °C for 24 h. For water deficit stress, water irrigation was stopped (for 7 days) until the soil water content was decreased to 40% of that under normal conditions.…”
Section: Methodsmentioning
confidence: 99%
“…S11, D-F, and S12, D-F). To test other genes that are directly or indirectly involved in ABA biosynthesis (Zang et al, 2016), we also examined the effect of Phytoene Synthase1 (SlPSY1) and Deetiolated1 (SlDET1) on the induction of VP in Cnr fruits. Silencing of SlPSY1 or SlDET1 intensified brown pigmentation in the outer epidermis of Cnr fruits (Supplemental Figs.…”
Section: Influences Of Slmet1 On the Expression Of Aba-related Genesmentioning
confidence: 99%